2014
DOI: 10.3354/esr00618
|View full text |Cite
|
Sign up to set email alerts
|

African forest elephant social networks: fission-fusion dynamics, but fewer associations

Abstract: For animal species with dynamic interactions, understanding social patterns can be difficult. Social network analysis quantifies associations and their intensity between individuals within a population, revealing the overall patterns of the society. We used networks to test the hypothesis that the elusive African forest elephant Loxodonta cyclotis exhibits fission−fusion social dynamics, similar to other elephant species. We observed associations between individuals in savanna clearings in Lopé National Park, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…2). Although the better-studied savanna elephant (Loxodonta africana) is a major driver of vegetation structure, tree recruitment, and plant community composition (e.g., Laws et al 1970;Guldemond & Aarde 2008;Asner & Levick 2012), studies of savanna elephants provide limited inference for understanding how forest elephants interact with their environment because the 2 taxa have demonstrable differences in morphology, ecology, reproduction, and social structure (e.g., Roca et al 2001;Schuttler et al 2014;Turkalo et al 2017). This is a problematic knowledge gap because forest elephants are ecosystem engineers that control, directly or indirectly, the availability of resources to other organisms by causing physical state changes in biotic and abiotic materials.…”
Section: Elephants As Ecological Engineers In a Time Of Crisismentioning
confidence: 99%
“…2). Although the better-studied savanna elephant (Loxodonta africana) is a major driver of vegetation structure, tree recruitment, and plant community composition (e.g., Laws et al 1970;Guldemond & Aarde 2008;Asner & Levick 2012), studies of savanna elephants provide limited inference for understanding how forest elephants interact with their environment because the 2 taxa have demonstrable differences in morphology, ecology, reproduction, and social structure (e.g., Roca et al 2001;Schuttler et al 2014;Turkalo et al 2017). This is a problematic knowledge gap because forest elephants are ecosystem engineers that control, directly or indirectly, the availability of resources to other organisms by causing physical state changes in biotic and abiotic materials.…”
Section: Elephants As Ecological Engineers In a Time Of Crisismentioning
confidence: 99%
“…Genetic studies have confirmed that individuals in these small groups are usually highly related 82 (Munshi-South 2011, Schuttler et al 2014a, Schuttler et al 2014b). Studies of forest elephants in 83 bais have also revealed that while forest elephant groups differ in size compared to savanna 84 elephant groups, both species exhibit fission-fusion social structure Lee 2013, 85 Schuttler et al 2014b).…”
Section: Introduction 58mentioning
confidence: 97%
“…Genetic studies have confirmed that individuals in these small groups are usually highly related [7,20,21]. Studies of forest elephants in bais have also revealed that while forest elephant groups differ in size compared to savanna elephant groups, both species exhibit fission-fusion social structure [2,7]. Collectively, these data have furthered our understanding of forest elephant sociality; however, many of these studies have relied on observations of forest elephants in bais.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, this last factor limits most behavioral observations of this species to time spent in bais (i.e. forest clearings around a water resource) [2][3][4], although observations have been possible when the elephants occupy coastal or savanna habitats [5][6][7][8]. Studies of African forest elephants are critical given their conservation status and recently documented population declines [9,10], as well as their relevance for understanding the evolution of proboscideans [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation